Enhanced thermal stability photophysical properties of photoselective PMMA/ITO nanohybrid films for greenhouse cooling in hot climates - Mohammed Alyami; Samah El-Bashir (Journal of Saudi Chemical Society)
The current research proposed innovative photoselective greenhouse cooling films made from PMMA/ITO nanohybrids, incorporating varying concentrations of Indium tin oxide nanocrystals (ITO NCs) and the fluorescent organic dye Lumogen F Red300, utilizing the solvent casting method. The morphology and structure were examined using transmission electron microscopy (TEM) and X-ray diffraction (XRD), demonstrating good homogeneity and amorphous nature. The impact of different ITO NC concentrations on physical properties was examined through differential scanning calorimetry (DSC), optical absorption, transmission, reflection, fluorescence, and Fourier transform infrared (FT-IR) spectroscopy. Integrating ITO NCs into the PMMA matrix showed enhanced thermal insulation capabilities of PMMA films while maintaining their transparency to photosynthetically active radiation (PAR). Maintaining this balance is crucial because it enables the films to selectively filter and reflect infrared radiation leading to lower greenhouse temperatures while still allowing the essential light needed for plant growth to pass through. This research is particularly significant for Sustainable Development Goals (SDGs) 2 and 13, especially in hot, water-scarce regions, as it protects plants from thermal stress, promotes growth, and supports food security in developing countries.